Effective degradation of curdlan powder by a novel endo-β-1→3-glucanase. (1st December 2018) - Li, Kuikui; Chen, Wei; Wang, Wenxia; Tan, Haidong; Li, Shuguang; Yin, Heng
Graphical abstract: Highlights: A novel glucanase with high activity to hydrolyse curdlan powder was identified. A novel curdlan pre-treatment method increase glucanase degradation rate. The degradation mode of glucanase was analyzed. Abstract: Curdlan is a water-insoluble microbial exo-polysaccharide that is hardly degraded. The gene CcGluE encoding an endo-β-1→3-glucanase consisting of 412 amino acids (44 kDa) from Cellulosimicrobium cellulans E4-5 was cloned and expressed in Escherichia coli . The recombinant CcGluE hydrolysed curdlan powder effectively. CcGluE shows high endo-β-1→3 glucanase activity and low β-1, 4 and β-1, 6 glucanase activities with broad substrate specificity for glucan, including curdlan, laminarin and β-1→3/1→6-glucan, and the highest catalytic activity for curdlan. Moreover, the hydrolytic products of curdlan were glucan oligosaccharides with degrees of polymerisation of 2–13, and the main products were glucobiose and glucotriose. Degradation mode analysis indicated that CcGluE is more likely to hydrolyse glucopentaose and revealed that CcGluE was an endo-glucanase. Furthermore, upon combination with a homogenising pre-treatment method with curdlan, the degradation efficiency of CcGluE for curdlan powder was greatly improved 7.1-fold, which laid a good foundation for the utilisation of curdlan.